SARS‐CoV‐2 infections in cancer outpatients—Most infected patients are asymptomatic carriers without impact on chemotherapy. (6th October 2020) - Hempel, Louisa; Piehler, Armin; Pfaffl, Michael W.; Molnar, Jakob; Kirchner, Benedikt; Robert, Sebastian; Veloso, Julia; Gandorfer, Beate; Trepotec, Zeljka; Mederle, Stefanie; Keim, Sabine; Milani, Valeria; et al.
Abstract: Oncologic patients are regarded as the population most at risk of developing a severe course of COVID‐19 due to the fact that malignant diseases and chemotherapy often weaken the immune system. In the face of the ongoing SARS‐CoV‐2 pandemic, how particular patients deal with this infection remains an important question. In the period between the 15 and 26 April 2020, a total of 1227 patients were tested in one of seven oncologic outpatient clinics for SARS‐CoV‐2, regardless of symptoms, employing RT‐qPCR. Of 1227 patients, 78 (6.4%) were tested positive of SARS‐CoV‐2. Only one of the patients who tested positive developed a severe form of COVID‐19 with pneumonia (CURB‐65 score of 2), and two patients showed mild symptoms. Fourteen of 75 asymptomatic but positively tested patients received chemotherapy or chemo‐immunotherapy according to their regular therapy algorithm (±4 weeks of SARS‐CoV‐2 test), and 48 of 78 (61.5%) positive‐tested patients received glucocorticoids as co‐medication. None of the asymptomatic infected patients showed unexpected complications due to the SARS‐CoV‐2 infection during the cancer treatment. These data clearly contrast the view that patients with an oncologic disease are particularly vulnerable to SARS‐CoV‐2 and suggest that compromising therapies could be continued or started despite the ongoing pandemic. Moreover the relatively low appearance of symptoms due to COVID‐19 among patients on chemotherapy and other immunosuppressive co‐medication like glucocorticoids indicate that suppressing the response capacity of the immune system reduces disease severity. Abstract : Largely unexpected, only 78 of 1227 tested cancer patients showed a COVID‐19 infection of which only three patients were symptomatic, ranging from mild symptoms to pneumonia. These data clearly contrast the view that oncology patients are particularly vulnerable to SARS‐CoV‐2 and suggest that necessary chemotherapies could be continued or started despite the ongoing pandemic. One explanation could be the immunosuppressive effect of simultaneous systemic therapy which will be further investigated.